(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The English language is indistinguishable from India, which has 23 provincial dialects and another 2,000 territorial dialects. However, it is difficult to have a public language in a country like India. The colonialist has provided us with a language known to the world called English because, in one way or another, we have plundered the laudable destiny of India with a country like India, its quality to the next piece of the universe. This article discusses writing in relation to Indian writing in English and the territorial writing of India in light of Indian English. IWE claims to have the predominance of local indigenous writing and overshadowed it with the post-pilgrim writing relationship. Since IWE is certainly not another substance, it is a mixture of Indian diaspora fiction in English that makes a great contribution to IWE. Again, regional writing chokes on inhalation without finding enough people to recharge its batteries and spread its scent like IWE around the world.